2016
DOI: 10.1016/j.jvs.2015.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cognitive status on exercise performance and quality of life in patients with symptomatic peripheral artery disease

Abstract: Purpose We determined whether scores on a cognitive screening measure were associated with the primary outcome measure of peak walking time (PWT) and with secondary outcome measures related to mobility, community-based ambulation, health-related quality of life (QoL), and vascular function in patients with claudication and PAD. Methods Gross cognitive status of 246 PAD patients was assessed with the Mini-Mental State Examination (MMSE) questionnaire. Patients were grouped according to whether they had a perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…We have previously found that metabolic syndrome 21 and lower cognitive status 22 are both negatively associated with HRQoL in symptomatic patients with PAD, and another investigation found that hypertension is negatively associated with overall quality of life and general health. 18 However, the identification of factors associated with baseline HRQoL in symptomatic patients with PAD has been primarily limited to PAD-specific markers, and has rarely considered comorbid conditions, 18 patient-based measures of overall physical function, and objective measurements of physical activity level.…”
Section: Introductionmentioning
confidence: 95%
“…We have previously found that metabolic syndrome 21 and lower cognitive status 22 are both negatively associated with HRQoL in symptomatic patients with PAD, and another investigation found that hypertension is negatively associated with overall quality of life and general health. 18 However, the identification of factors associated with baseline HRQoL in symptomatic patients with PAD has been primarily limited to PAD-specific markers, and has rarely considered comorbid conditions, 18 patient-based measures of overall physical function, and objective measurements of physical activity level.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, confirming experimental data, clinical trials have shown the presence of cerebrovascular disease in the context of PAD [26,27,28,29]. Thus, compared to hypertensives and normotensives patients, patients with PAD had significantly lower performance on seven tests of nonverbal memory, concentration, executive function, perception-motor speed, and manual dexterity.…”
Section: Cognitive Function In Patients With Peripheral Arterial Dmentioning
confidence: 66%
“…In a study conducted by Gardner et al [28], patients with PAD were grouped according to their performance on a mini-mental state examination (MMSE). Patients who scored at least 28 out of 30 points on MMSE underwent an assessment of several aspects, including peak walking time and health-related quality of life.…”
Section: Cognitive Function In Patients With Peripheral Arterial Dmentioning
confidence: 99%
“…The majority ( n = 129, 70.5%) of the included studies' populations were older adults with no defined conditions. The remaining 54 articles (29.5%) included older adults with dementia or cognitive impairment, 34–59 fragile X syndrome associated with tremor/ataxia, a condition resulting from a gene permutation, 60 stroke, 61,62 chronic obstructive pulmonary disease, 63 cancer, 64,65 diabetes, 66 Parkinson's disease, 17,67–74 cardiovascular disease, 14,75–80 lower back pain, 81 multiple comorbidities 82–84 and post‐menopausal conditions 85 . Most studies recruited participants from the community ( n = 164, 89.6%), and the remaining studies ( n = 19, 10.4%) recruited from the hospital and long‐term care setting or both the long‐term care and community setting, or did not report the setting from which the participants were recruited.…”
Section: Resultsmentioning
confidence: 99%